1970
DOI: 10.1161/01.res.26.6.771
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Triglyceridemia in Hypercholesterolemic Rabbits

Abstract: To elucidate mechanisms responsible for the increased plasma triglyceride (TG) which occurs in diet-induced hypercholesterolemia in rabbits, albino rabbits were fed a 3% cholesterol diet for various durations, and the following determinations were carried out: plasma lipid levels; turnover rate of plasma TG (labeled very low density lipoprotein, or glycerol-2-3 H method); lipoprotein lipase activity of the heart and plasma; fatty acid and acetate incorporation into TG in the liver (homogenates and slices). Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1972
1972
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Chloroform-methanol extraction procedures (Folch et al, 1957;Bligh & Dyer, 1959;Hajra et al, 1968;Eibl et al, 1969;Huang & Kako, 1970) constantly produced a high control value in the presence of subcellular fractions before incubation. Radioactivity was high and variable, even when the tissue fraction was omitted from the incubation mixture, which was probably due to non-specific binding of albumin (Barden & Cleland, 1969).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chloroform-methanol extraction procedures (Folch et al, 1957;Bligh & Dyer, 1959;Hajra et al, 1968;Eibl et al, 1969;Huang & Kako, 1970) constantly produced a high control value in the presence of subcellular fractions before incubation. Radioactivity was high and variable, even when the tissue fraction was omitted from the incubation mixture, which was probably due to non-specific binding of albumin (Barden & Cleland, 1969).…”
mentioning
confidence: 99%
“…30-60°C)-diethyl ether-acetic acid (40:10:1, by vol.) (Possmayer & Mudd, 1971;Huang & Kako, 1970). The phospholipid and the neutral lipid fractions were eluted with chloroformmethanol (1: 1, v/v); the eluates were evaporated to a small volume under N2, and re-chromatographed in another system for further identification (see below).…”
mentioning
confidence: 99%
“…In the present study the clearing-factor lipase activity in heart and adipose tissue from obese mice has been measured by a new assay procedure. In addition the plasma concentration of cholesterol and triglycerides, both of which may induce changes in the activity of clearing-factor lipase (Fielding, 1970;Huang & Kako, 1970;Shafrir & Biale, 1970), have been measured in an attempt to determine what modifiers of clearing-factor lipase are responsible for the changes in activity observed under different physiological conditions.…”
mentioning
confidence: 99%
“…A pure type of hypercholesterolemia with normal tri glyceride level is known. However, it has been demonstrated that prolonged feeding of high cholesterol diet induces the elevation of serum triglyceride in rabbits 14 and that high concentration of serum cholesterol inhibits lipoprotein li- Daily oral administration of 300 mg of moctamide completely inhibited the elevation of serum cholesterol due to the egg yolk feeding. In the case of two subjects, serum cholesterol was lower than initial levels after the drug, though the same amount of egg yolk was ingested in this period (Table III).…”
Section: Discussionmentioning
confidence: 99%